Multipath Pipelined Polyphase Structures for FIR Interpolation and Decimation in MIMO OFDM Systems. (29th December 2011) - Zhang, Zhen-dong; Wu, Bin; Zhou, Yu-mei
Abstract : The combination of multiple-input multiple-output (MIMO) signal processing with orthogonal frequency-division multiplexing (OFDM) technique is one favored solution in wireless communication systems for enhancing data rate. However, the computational complexity is also linear increased with the number of data streams. Generally, multiple finite impulse response (FIR) interpolations and decimations are added to solve the multiple data streams in a MIMO OFDM system, which cause a large increase in the hardware cost. In this paper, two multipath pipelined polyphase structures for FIR interpolation and decimation to efficiently deal with the simultaneous multiple data streams are proposed. According to the proposed structures, M simultaneous data streams can be supported in the M -component polyphase interpolation or decimation with only one set of computation units. Implementation examples show that up to 56% reduction of silicon area can be obtained over the traditional polyphase structures.